2007
DOI: 10.1007/s00213-007-0859-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory impairment in “ecstasy” (MDMA) users

Abstract: Prospective memory performance is sensitive to regular and even moderate ecstasy use. Importantly, ecstasy users experience generalized difficulties with prospective memory, suggesting that these deficits are likely to have important implications for day-to-day functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
66
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 38 publications
9
66
3
Order By: Relevance
“…Self report measures of this construct have been developed (e.g., Crawford et al, 2005;Hannon et al, 1995) and in previous research from our laboratory, Fisk and co-workers have demonstrated apparent impairments on these measures among ecstasy/polydrug users (Montgomery & Fisk, 2007) and cannabis only users (Fisk & Montgomery, 2008). Other researchers have also reported deficits on self report PM measures among users of illicit drugs (Heffernan et al, 2001a;2001b;Rodgers et al, 2001; and studies from our own laboratory and elsewhere have revealed deficits among illicit drug users in laboratory measures of PM (Hadjiefthyvoulou et al, in press;Rendell et al, 2007a;Rendell et al, 2009). …”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Self report measures of this construct have been developed (e.g., Crawford et al, 2005;Hannon et al, 1995) and in previous research from our laboratory, Fisk and co-workers have demonstrated apparent impairments on these measures among ecstasy/polydrug users (Montgomery & Fisk, 2007) and cannabis only users (Fisk & Montgomery, 2008). Other researchers have also reported deficits on self report PM measures among users of illicit drugs (Heffernan et al, 2001a;2001b;Rodgers et al, 2001; and studies from our own laboratory and elsewhere have revealed deficits among illicit drug users in laboratory measures of PM (Hadjiefthyvoulou et al, in press;Rendell et al, 2007a;Rendell et al, 2009). …”
mentioning
confidence: 63%
“…It is the while others areremaining more irregular tasks with that have a more substantial learning requirement. Interestingly ecstasy users performed worse on these irregular virtual week tasks recording 65% of the level of correct responses achieved by nonusers while for regular tasks the percentage was 83% (computed from Table 2; Rendell et al, 2007a). This suggests that performance is indeed adversely affected by the learning component.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Although Rendell et al (2007) did not report effects in relation to lifetime dose, they found that frequent ecstasy users (using more than once a fortnight) performed worse than infrequent users (using less than one a month) who in turn performed worse than nonusers on all PM measures on the virtual week task.…”
mentioning
confidence: 85%